History of health, a valuable tool in public health. Issue 9 (1st September 2001) - Perdiguero, E; Bernabeu, J; Huertas, R; Rodríguez-Ocaña, E
Abstract : The aim of this article is to highlight the importance of the history of public health for public health research and practice itself. After summarily reviewing the current great vitality of the history of collective health oriented initiatives, we explain three particular features of the historical vantage point in public health, namely the importance of the context, the relevance of a diachronic attitude and the critical perspective. In order to illustrate those three topics, we bring up examples taken from three centuries of fight against malaria, the so called "re-emerging diseases" and the 1918 influenza epidemic. The historical approach enriches our critical perception of the social effects of initiatives undertaken in the name of public health, shows the shortcomings of public health interventions based on single factors and asks for a wider time scope in the assessment of current problems. The use of a historical perspective to examine the plurality of determinants in any particular health condition will help to solve the longlasting debate on the primacy of individual versus population factors, which has been particularly intense in recent times.